PO 113 - ANAESTHETIC MANAGEMENT OF A PATIENT WITH DEEP BRAIN STIMULATION IMPLANT FOR TOTAL PAROTIDECTOMY - Roxo, Miguel; Almeida, Carolina; Spencer, Leina (Journal of the Portuguese Society of Anesthesiology, 2023)
x